Energy, exergy, and emission analysis of a hydroxyl fueled compression ignition engine under dual fuel mode. (1st April 2020) - Kumar Sharma, Pushpendra; Sharma, Dilip; Lal Soni, Shyam; Jhalani, Amit; Singh, Digambar; Sharma, Sumit
Highlights: Effects of hydroxyl gas addition on performance, emission, and combustion was assessed. BTE is improved with increase in HHO energy share. Significant reduction in HC, CO, and smoke emissions. Exergy improved in brake power, exhaust gas, and heat transfer. Abstract: In this study, energy, exergy, and emission analysis were investigated for the hydroxyl fueled compression ignition (CI) engine under dual fuel mode. Hydroxyl gas (HHO) generator was used to supply three different mass flow rates of HHO (0.25, 0.5, and 0.75 lpm) along with diesel for the experimental work on a modified constant speed CI engine. Significant improvement of 6.5% in brake thermal efficiency was obtained with 0.75 lpm HHO flow rate at 80% load. However, a slight increment in heat transfer losses and energy in exhaust gas were observed by 6.29% and 8.55%, respectively, at the optimized condition. The work availability, exhaust gas, and heat transfer exergy were increased by 6.54%, 5.69%, and 6.36% (0.75 lpm and 80% load), respectively due to the higher diffusivity of hydrogen and faster oxidation of fuel species within the cylinder. A significant reduction in emission parameters was obtained in carbon monoxide, unburnt hydrocarbon, and smoke emission as 53%, 62%, and 49%, respectively. High pressure and temperature within the cylinder improve the rate of oxidation of fuel species, which results in decreased HC, CO, and smoke emission. Furthermore, high temperature increases the NOX emission by 35%. Overall it can be concluded the HHO can be used as a prominent alternative fuel with increased exergy and lower emissions.